Development of simple method for the determination of 5-Methyl tetrahydrofolate in Dried Blood Spot by High Performance Liquid Chromatography (HPLC) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Folate (Reduced) or folic acid (oxidized), is a water-soluble vitamin necessary for thymidylate synthase, methionine synthase, serine hydroxymethyltransferase, and folate deficiency associated with megaloblastic anemia, neural tube defect, and coronary heart disease. The available folate data is minimal due to a dearth of suitable, accurate, field-friendly blood collection and estimation methods. Conventional assays like microbiological and competitive protein-binding radioassay methods are used to estimate the total folate in serum and whole blood. In erythrocytes, folate exists mainly as 5-methyltetrahydrofolate polyglutamate and indicates the long-term storage of folate status. Therefore, the study aimed to develop a simple method for estimating 5-methyl tetrahydrofolate (5-MTHF) by high-performance liquid chromatography (HPLC) in dried blood spots (DBS) as an indicator of folate status. The present study results indicate standard 5-methyltetrahydrofolate with different concentrations with linear regression was showed R2-0.98, and the minimum detection limit of a standard was 20 pg. The inter-and intra-assay variations were found to be less than 10%. A good correlation (R2-0.964) between the DBS and blood and the recovery of added standard in the DBS sample was more than 80%. A minimum of three DBS punches equivalent to 20mL of blood was required for the analysis, and the competitive protein-binding radioassay showed slightly high folate compared to the HPLC method. The stability of 5-MTHF in DBS was also tested periodically. DBS technique and HPLC method are simple, sensitive, not expansive, and safe compared to the microbiological and competitive binding assay for assessing sub-clinical folate status in a field survey on a large population.